Pengaruh Karakteristik Kepribadian dan Kemampuan Intelektual terhadap Kinerja Pegawai pada Era Digital melalui Kompetensi Pegawai sebagai Variabel Intervening di BPSDM Provinsi Jambi - Umi Sodiyah; Zulfina Adriani; Dian Mala Fithriani (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
The purpose of this study was to determine the direct effect of personality characteristics and intellectual abilities on employee performance in the digital era and competence, the effect of competence on performance, and the indirect effect of personality variables and intellectual abilities on employee performance in the digital era through competence as an intervening variable in BPSDM Jambi Province. The type of research used is quantitative research with primary and secondary data. Sampling used a simple random sampling technique so that 65 employees were selected as respondents. Data collection used a questionnaire and data analysis used Smart PLS. The results of the analysis showed that personality characteristics directly affect performance and competence with a significance value of P <0.05, intellectual ability does not affect performance (P>0.05), but affects competence with a significance value of P <0.05, and competence affects the performance of BPSDM Jambi Province employees in the digital erawith a significance value of P <0.05. Furthermore, the direct effect shows that employee competence mediates the influence of personality characteristics and intellectual abilities on employee performance. This shows that personality characteristics and intellectual abilities affect performance through employee competence as an intervening variable.